2005
DOI: 10.3171/jns.2005.103.4.0597
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral acid—base homeostasis after severe traumatic brain injury

Abstract: Severe human TBI profoundly disturbs cerebral acid-base homeostasis. The observed pH changes persist for the first 24 hours after the trauma. Brain tissue acidosis is associated with increased tissue PCO2 and lactate concentration; these pathobiochemical changes are more severe in patients who remain in a persistent vegetative state or die. Furthermore, increased brain tissue PCO2 (> 60 mm Hg) appears to be a useful clinical indicator of critical cerebral ischemia, especially when accompanied by increased lact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
65
1
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 48 publications
0
65
1
4
Order By: Relevance
“…1) Increased astrocytic glycolysis as a result of increased excitatory amino acid, chiefly glutamate, necessitates rapid uptake from the ECF via Na ϩ -dependent co-transport. The resultant intracellular glutamate and Na ϩ increase activates Na ϩ /K ϩ -ATPase, which stimulates astrocytic glycolysis and production of lactate (20,(41)(42)(43). 2) Although less likely in the present study (i.e.…”
Section: Discussionmentioning
confidence: 48%
“…1) Increased astrocytic glycolysis as a result of increased excitatory amino acid, chiefly glutamate, necessitates rapid uptake from the ECF via Na ϩ -dependent co-transport. The resultant intracellular glutamate and Na ϩ increase activates Na ϩ /K ϩ -ATPase, which stimulates astrocytic glycolysis and production of lactate (20,(41)(42)(43). 2) Although less likely in the present study (i.e.…”
Section: Discussionmentioning
confidence: 48%
“…15,20 It has also been previously demonstrated that following human TBI, acidosis is associated with deranged lactate metabolism and increased mortality. 18,21,22 However, the relationship between hypoxia and acidosis and their impact on energy metabolism, including other biochemical markers, in our view warrants further exploration. The aim of the present study was, therefore, to test the hypothesis that the presence of cerebral acidosis with or without hypoxia indicates a more profound metabolic derangement, compared with the periods of hypoxia without acidosis or when normal oxygenation and pH are present.…”
Section: Introductionmentioning
confidence: 79%
“…Although many of the mechanisms above rely on intracellular pH changes, it has been shown that an intracellular pH is strongly dependent on the regulation of extracellular pH. 13 Despite differences in the methods of measurement, there is ample evidence in human studies as well as in experimental models of ischemia, 14,15 for the temporary reduction in cerebral extracellular pH (pH bt ) after cerebral insults such as TBI [16][17][18][19] and subarachnoid hemorrhage. 15,20 It has also been previously demonstrated that following human TBI, acidosis is associated with deranged lactate metabolism and increased mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Having their terminals outside the blood-brain barrier and exposed to circulating pathogens and toxins, magnocellular neurons are positioned to be sentinel monitors and first defenders, modulating the innate immune response and protecting the CNS from injury. A more complete understanding of the neural networks and molecular and cellular changes involved could enhance recovery of patients after traumatic brain injury in which acidosis leads to neuronal death (23,100), with an elevated lactate/pyruvate ratio in microdialysates predictive of a less favorable outcome (70). Identifying a mechanism and site of osmotic protection will likewise benefit trauma patients, particularly those with hemorrhagic shock, in which HS provides a more balanced inflammatory response and may attenuate life-threatening multiorgan dysfunction (90).…”
Section: Perspectives and Significancementioning
confidence: 99%
“…Acidosis is a major factor spreading brain damage following ischemia and traumatic head injury in humans. Resulting from failure to maintain cellular ATP levels with loss of membrane integrity, the induced ionic imbalances produce metabolic acids that decrease both intracellular and extracellular pH adjacent to the cerebral infarct (100) and the traumatized brain (23). To our knowledge, this is the first report showing activation of the brain's innate immune response by microdialyzing an acidic perfusion fluid in the SON area, thereby identifying a new animal model for probing the pathophysiology and recovery from acidosis following injury by stroke and trauma.…”
mentioning
confidence: 99%